2017
DOI: 10.1186/s40200-017-0293-7
|View full text |Cite
|
Sign up to set email alerts
|

Zinc and curcumin lower arylsulfatses and some metabolic parameters in streptozotocin-induced diabetes

Abstract: In rats with induced diabetes, Zinc and curcumin treatment showed a significant increase of catalase and a significant decrease of glucose, lipid profile components and arylsulphatases activity compared to the untreated rats. We suggest that dietary zinc and curcumin are promising protective agents for reducing the metabolic defect of diabetes. Dear Editor;Diabetes mellitus is a metabolic disease and the pathogenesis of diabetes mellitus is implicated in the oxidative stress and the generation of superoxide fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The mechanism by which curcumin provides its hypoglycemic effect has been reported previously. Recent studies by ourselves and others showed that curcumin and zinc can ameliorate hyperglycemia in diabetic rats 20 , 37 . Also, oral administration of ZnONPs could inhibit the intestinal α-glucosidase enzyme and so reduce glucose absorption and it might enhance glycolysis 19 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The mechanism by which curcumin provides its hypoglycemic effect has been reported previously. Recent studies by ourselves and others showed that curcumin and zinc can ameliorate hyperglycemia in diabetic rats 20 , 37 . Also, oral administration of ZnONPs could inhibit the intestinal α-glucosidase enzyme and so reduce glucose absorption and it might enhance glycolysis 19 .…”
Section: Discussionmentioning
confidence: 96%
“…Although the antidiabetic activities of CurNPs and ZnONPs were observed in previous studies, the underlying molecular mechanisms, safety doses, and therapeutic efficacies of these nanoparticles were not fully determined. In our previous work, we proved the antidiabetic effect of dietary zinc and curcumin to control diabetes in rats with some toxicity 20 . Upon these bases, our work was designed to evaluate a powerful antidiabetic agent with minimal toxicity using nanotechnology.…”
Section: Introductionmentioning
confidence: 95%
“…Oxidative stress increased ROS levels that consequently inhibited the activities of antioxidant enzymes [ 10 ]. In addition, inhibition of SOD activity was associated with the accumulation of superoxide ions that consequently inactivated GPx and increased H 2 O 2 level [ 10 , 11 , 20 , 21 ]. Following cell membrane structural damage due to the presence of excessive amounts of ROS, the membrane permeability increased and some of the intracellular enzymes like Ck-MB, CPK, and LDH leaked from the cell [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was shown that the death of isolated β-cells and dysfunction could be prevented by CUR in diabetic STZ-induced animals [39]. Balbaa et al [40] showed a considerable boost in the plasma glucose level in animals after STZ vaccination. It has been found that zinc deficiency and altered zinc metabolism are linked to reduced glucose tolerance [41].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, after treating the rats with Zn, the serum HDL-C level was significantly augmented [42]. In short, CUR treatment in diabetic rats could appreciably lower the serum TC and TG concentrations [36,40]. Table 4 described the influence of CUR+ZnCl2 on the serum AST and ALT contents in STZ induced diabetic rats.…”
Section: Resultsmentioning
confidence: 99%